STUDY ON CONTACT STRESS OF BEVELOID GEAR BASED ON FRACTAL THEORY - LIU YongPing; WEI Shuai; DONG ChangBin; WEI YongQiao; REN ZhongTao; LI ZeYu (Jixie qiangdu)
In order to more accurately reflect the real contact stress on the tooth surface of beveloid gear, this paper constructs the tooth surface contact coefficient of beveloid gear, and verifies its rationality. Based on fractal contact theory and Hertz contact theory, a contact model of beveloid gear is established, which comprehensively considers the parameters such as gear tooth surface roughness, elastic deformation of contact point and material characteristics. The effectiveness of this method is contact strength of beveloid gear, which is compared with the finite element calculation results by calculating. The relation between load and area during gear meshing is obtained through fractal theory, and four basic parameters are simulated to analyze the effect of fractal contact model. The results show that the accuracy of fractal contact model is verified by numerical simulation and analysis of the relation between actual contact area and load. This paper is based on the finite element theory, Hertz contact theory and fractal theory, the tooth surface contact strength of beveloid gear is compared and analyzed, the correctness of calculating the contact stress of beveloid gear by fractal contact model is verified. The establishment of this model provides a certain theoretical basis for the design and strength check of beveloid gear.